(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2025)
Small-scale pepper farmers, particularly in Tuai Rumah Mawas, face persistent challenges in efficiently detaching pepper from their stalks, especially during peak harvesting seasons. Current manual methods are highly labour intensive, time consuming, and unsustainable for long term agricultural productivity. Furthermore, traditional wooden sorting tools deteriorate quickly due to constant exposure to moisture and seasonal flooding, further exacerbating post-harvest inefficiencies. This study aims to design a semi-automated pepper stalk separation machine that addresses the post-harvest constraints faced by smallholder farmers, with the specific objective of increasing processing capacity and reducing dependency on manual labour. The machine is designed to operate on a standard 230V power supply with a motor speed of 1400 rpm, capable of processing up to 50 kg of pepper within 30 minutes. The design incorporates corrosion-resistant materials for enhanced durability and ergonomic features to ensure safe and user-friendly operation. Preliminary performance assessments indicate that the machine can reduce labour costs by up to 85% and achieve a processing throughput of approximately 1.67 kg/min, thereby significantly improving productivity and sustainability for rural pepper farming communities.